Screening for cognitive impairment in older adults with hematological malignancies using the Montreal Cognitive Assessment and neuropsychological testing. Issue 2 (March 2020) - Koll, Thuy T.; Sheese, Amelia Nelson; Semin, Jessica; Ernst, Weston; High, Robin; Wildes, Tanya M.; Fisher, Alfred; Murman, Daniel L.
Abstract: Objectives: The primary objective of the current study is to describe the prevalence and profile of cognitive domains affected in older adults with hematological malignancies evaluated for hematopoietic cell transplantation (HCT) using the Montreal Cognitive Assessment (MoCA) and neuropsychological tests. The secondary objective is to determine if a specific MoCA cut-off score would correlate with the identification of cognitive impairment detected by neuropsychological tests. This would facilitate interpretation of cognitive screening and referral of patients who would likely need further neuropsychological testing. Materials and Methods: Fifty-one patients 60 years and older who were evaluated for HCT were assessed using a battery of standardized neuropsychological tests and MoCA. We analyzed Receiver Operating Characteristics (ROC) comparing MoCA scores and four different neuropsychological test criteria for cognitive impairment. Results: The prevalence of cognitive impairment detected by neuropsychological tests was 53 to 70.6% using the criteria for patients with cancer by the International Cancer Cognition Task Force (ICCTF). The following cognitive domains were most affected: language, learning and memory, visuospatial skills, and executive function. MoCA is an appropriate screening test for cognitive impairment. Using the ICCTF criteria, 86 to 100% of patients are correctly classified as having significant cognitive impairment on neuropsychological tests using a cut-off score of 20 or less. Conclusion: There is a high prevalence of cognitive impairment identified by neuropsychological tests in older patients with hematological malignancies evaluated for HCT. Identification of an appropriate MoCA cut-off score in this population is important to identify patients who would benefit from further assessment.